English ID 2A : Student's book & Workbook - Seligson, Paul; Lethaby, Carol; Barros, Luiz Otávio; Abraham, Tom (Ho Chi Minh City Vietnam News Agency Publishing House, 2018)
English ID is a brand new four-level series for young adults and adults with an emphasis on speaking both accurately and fluently.The material builds on students' existing knowledge of English and introduces new language through authentic texts and audiovisual material, including actual YouTube videos and the engaging ID café, a tailor-made sitcom-style video. With its user-friendly format, English ID is a highly flexible course which offers 80-120 hours of material.
Keywords: Cơ bản